The Influence of Trust and Satisfaction on Customer Retention of PT. Askrida Syariah Insurance Medan Branch - Bayu Prabowo; Tri Inda Fadhila Rahma (Penerbit Jurnal Indonesia, 2022)
This study aims to analyze: (1) The effect of trust on customer retention Askrida insurance. and the effect of satisfaction on customer retention for Askrida insurance. The population in this study are customers who have used the services of PT. Asuransi ASKRIDA SYARIAH Medan Branch for more than 1 year or more. The sampling technique used is purposive sampling. The types of data used in this study are primary and secondary data. The data analysis technique used descriptive and inductive analysis through multiple regression analysis using the SPSS version 22.00 program. The results of this study indicate that: (1) Trust has a positive and significant effect on customer retention of PT. Asuransi Bangun ASKRIDA SYARIAH Medan branch, (2) Satisfaction has a positive and significant effect on customer retention of PT. Asuransi ASKRIDA SYARIAH Medan branch.